2010
DOI: 10.5424/fs/2010193-8927
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vegetation management and fertilization on Pinus pinaster growth and on understory biomass and composition

Abstract: To study the influence of understory vegetation management and fertilization, on pine growth and competing vegetation, a field trial was established in a 6-year old pine forest. Treatments included: control (C), vegetation cutting and removal, with and without fertilization (CRF and CR treatments), vegetation chipping, with and without fertilization (CDF and CD treatments). Treatments were replicate three times and arranged in completely randomized blocks. Pine volume was determined between 2002 and 2007 and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Biomass compensation for understory removals occurs significantly in BF, but not in BKF and LF after treatment. In an arid region forest, the researchers found the degree of biomass compensation was dependent on restoration term (Canteiro et al, 2011) and a fertilized environment (Pires and Xavier, 2010) after the removal, and they observed that there was a compensation for removals under high fertilization during the first 3 years but was reduced compensation after 9 years. Moreover, biomass compensation for plant removals can occur relatively rapidly in temperate ecosystems (Gonzalez et al, 2019).…”
Section: Changes In Understory Diversity and Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass compensation for understory removals occurs significantly in BF, but not in BKF and LF after treatment. In an arid region forest, the researchers found the degree of biomass compensation was dependent on restoration term (Canteiro et al, 2011) and a fertilized environment (Pires and Xavier, 2010) after the removal, and they observed that there was a compensation for removals under high fertilization during the first 3 years but was reduced compensation after 9 years. Moreover, biomass compensation for plant removals can occur relatively rapidly in temperate ecosystems (Gonzalez et al, 2019).…”
Section: Changes In Understory Diversity and Biomassmentioning
confidence: 99%
“…This contrasting finding is because it not only elicits significant increases in photosynthetic characteristics (Kume et al, 2003) but also reduces drought stress, resulting in an increased allocation of carbon into below-ground organs (Vandenberghe et al, 2006). Moreover, other researchers have argued that understory removal can prevent nutrient output and limit the build-up of litter and light distribution (Motsinger et al, 2010), thereby limiting plant recruitment (Premer et al, 2016) and ultimately leading to a decrease in understory biomass (Pires and Xavier, 2010). These contradictory reports on the effects of understory management on the understory characteristic may be attributed to differences in forest stand and types (Premer et al, 2016) and ages (Yildiz et al, 2011;Zhou et al, 2018b), the number (Dupuy and Chazdon, 2008) and times (De Lombaerde et al, 2021) of understory management, and vegetation types (Copeland et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the addition of N, P, and K, together or individually, increases the wood production of species such as eucalyptus or maritime pine in less fertile soils (Bonneau, 1995;Sette Júnior, 2010;Pires and Xavier, 2010;Camargo, 2013). The influence of adding nutrients is considered more effective at juvenile stages than at maturity.…”
Section: Effects Of the Fertilizers On The Size And Growth Of The Treesmentioning
confidence: 99%
“…El abandono de tierras agrícolas no es un problema solo en España, en las últimas décadas se han forestado terrenos agrícolas abandonados en diversas partes del mundo, tanto en nuestro continente (Portugal, Francia, etc. ), como en otros, Australia, América y África, existiendo diferentes trabajos que muestran los resultados, pero también las inquietudes sobre el futuro de estas forestaciones en cuanto a gestión y biodiversidad (Lemieux and Delisle, 1998;Chapman and Chapman, 1999;Brockerhoff et al, 2008;Kushla, 2009;Pires and Xavier, 2010;Bremer and Farley, 2010).…”
Section: Introductionunclassified